2017
DOI: 10.1186/s12913-017-2673-6
|View full text |Cite
|
Sign up to set email alerts
|

Does having a usual primary care provider reduce patient self-referrals in rural China’s rural multi-tiered medical system? A retrospective study in Qianjiang District, China

Abstract: IntroductionWithin China’s multi-tiered medical system, many patients seek care in higher-tiered hospitals without a referral by a primary-care provider. This trend, generally referred to as patient self-referral behavior, may reduce the efficiency of the health care system. This study seeks to test the hypothesis that having a usual primary care provider could reduce patients’ self-referral behavior.MethodsWe obtained medical records of 832 patients who were hospitalized for common respiratory diseases from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…Family doctor system, which has been shown to play an important role in gatekeeping function of PCIs (30,31), was not an influencing factor in our study. Da Feng et al found that family doctors may reduce patients' tendency for unnecessary use of medical resources (32). However, according to our finding, family doctors were not playing a role in guiding healthcare seeking behaviors of patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Family doctor system, which has been shown to play an important role in gatekeeping function of PCIs (30,31), was not an influencing factor in our study. Da Feng et al found that family doctors may reduce patients' tendency for unnecessary use of medical resources (32). However, according to our finding, family doctors were not playing a role in guiding healthcare seeking behaviors of patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Some countries allow participants to directly access advanced health facilities' fee-for-service payments while other countries continue to implement gate keepers and tiered referrals. China launched health service reforms by reintroducing the tiered referral system as a solution to reduce over-utilization in regional hospitals and control the cost of health services (Feng et al, 2017). Unfortunately, the results of this study suggest that tiered referral in secondary health facilities makes lead to overutilization.…”
Section: 23mentioning
confidence: 74%
“…With a study showing that patients with primary care providers are likely to reduce patient self-referrals in rural China's rural multi-tiered medical system (Feng et al, 2017) and another study showing that general practitioners (GPs) can effectively reduce patient referral behavior, health maintenance organizations (HMOs) in the United States require patients to consult a primary care physician firstly before considering a referral (Sekhri, 2000;Hoel et al, 2021). Many European countries have GP systems that can effectively guide patients through graded care (Verhaak et al, 2004;Brown et al, 2014).…”
Section: Discussion the Effect Of Having A Usual Primary Care Provider On Polypharmacy Behaviorsmentioning
confidence: 99%